Literatur Review : Peran Anti-Hipertensi dalam Penurunan Tekanan Darah (Al GIZZAI: PUBLIC HEALTH NUTRITION JOURNAL, 2022)
Hypertension is a silent killer because many sufferers do not show symptoms before reaching severe Hypertension is a silent killer because many sufferers do not show symptoms before reaching serious conditions and even complications to death. The purpose of this review article is to analyze the use of herbal ingredients in the treatment of hypertension. This study used a literature study method from eight articles that matched the initial screening criteria. The results showed anti-hypertensive from eight natural herbal ingredients that functioned as anti-hypertensive both for treatment and for prevention towards the degree of severe hypertension. Furthermore, this study used as the basis for the development of herbal anti-hypertensives.